Reduction in concentration of chromium (VI) by Lysinibacillus macroides isolated from sediments of the Chapala Lake, Mexico - Hernández-Peña, Claudia Carolina (2021)
The Chapala Lake is one of the most polluted lakes in Mexico, due to the in fl ow of effl uents from several industrial plants, the lake accumulates pollutants such as chromium(VI) which is considered important for aquatic ecosystem. This study aimed was to evaluate the ability to decrease the concentration of chromium (VI) by Lysinibacillus macroides 2(1B)104A, isolated from sediments of the Chapala Lake. The strain was identifi ed through 16S rRNA sequencing and phylogenetic analysis. Results showed that this strain grows in concentrations of 50, 100, 200 and 300 mgL-1 Cr(VI), in pH ranging 6 to 7, showing 79.508% reduction in concentration 50 mgL-1, determining that the reduction occurs extracellularly. Likewise, it was observed that Lysinibacillus macroides reduced the concentration of Cr(IV) in the broth, it was not observed that the bacteria could sequester Cr(VI) in the membrane or intracellularly. However, it reduced the concentration of Cr(VI) in the broth. Lysinibacillus macroides 2(1B)104A isolate showed having the ability that decrease the concentration of Cr(VI), which makes it a viable options for bioremediation of water polluted with this metal.